Interpreting Between Greek Sign Language and Spoken Greek at the Aristotle University of Thessaloniki - Kassapi, Eleni; Efklides, Anastasia; Polatoglou, Hariton; Myronidou, Maria; Papaioannou, Maria (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2005)
AbstractThis paper presents the first project on the formation of Sign Language Interpreters in Greek Universities. At the Aristotle University of Thessaloniki, the training of sign language interpreters is an experimental project organized by the Social Policy Committee and is carried out in collaboration with the School of English Studies and the Postgraduate Program in Translation and Interpretation Studies. This project has been initiated because of the realization that deaf students represent a linguistic minority in our University. In universities, the growing number of deaf students increases the demand for community and conference interpreting between the Greek sign language and the Greek — general or special — spoken language.